Using RE-AIM to examine implementation of a tele-nephrology program for veterans living in rural areas - Mattocks, Kristin M.; Kroll-Desrosiers, Aimee; Crowley, Susan; Tuozzo, Katherine; Rifkin, Ian; Moore, David; Walker, Lorrie; Bonegio, Ramon (Frontiers in Health Services, 2023)
Introduction Chronic kidney disease (CKD) and refractory hypertension (rHTN) are common, chronic conditions that affect 10%–16% of Veterans. Several small studies have suggested that tele-nephrology can deliver nephrology care effectively to rural Veterans. The purpose of this evaluation was to examine perceptions and experiences with this tele-nephrology program among spoke site staff and clinicians using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework to guide our understanding of tele-nephrology implementation. Methods We conducted semi-structured interviews with fourteen clinicians at five tele-nephrology spoke sites. We used content analysis to analyze the results using our RE-AIM framework. Results Five major themes arose: (1) Active engagement of a centralized clinical champion was a key factor in early success of tele-nephrology program; (2) Transition from community-based nephrology to VA tele-nephrology was heralded as the most meaningful indicator of the effectiveness of the intervention; (3) Effective adoption strategies included bi-weekly training with Hub nephrology staff and engagement of a local renal champion; (4) Meeting the needs of Veterans through proper staffing during tele-nephrology examinations was a key priority in facility program implementation; and (5) Growing reliance on Hub nephrologists may give rise to insufficient availability of nephrology appointments in some Spoke sites. Discussion This evaluation represents an important step forward as VA considers how to provide care to Veterans at facilities without VA specialty providers. The COVID-19 pandemic has drastically shifted options for Veterans, and increasingly, the VA is moving to shift care from community to VA via virtual care. Further research should examine how the VA manages potential problems related to access to virtual providers and examine Veteran perspectives on community in-person vs. virtual VA care.